2013
DOI: 10.1089/vbz.2012.1131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotype Distribution of Chlamydia psittaci in Feral Canada Geese (Branta canadensis) in Belgium

Abstract: Chlamydia psittaci is a zoonotic pathogen with a wide range of avian hosts and worldwide geographical spread. Zoonotic transfer occurs by inhalation or direct contact and may cause psittacosis or parrot disease. Host reservoirs of particular epidemiological interest include gregarious or migratory species, as colonial behavior facilitates microbial spread amongst conspecifics and a migratory ecology permits disperse over a wide geographic region. The current study detected C. psittaci antibodies in 76 of 81 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The authors concluded that Canada geese are indeed part of the avian reservoir host system for this bacterium, and that they hence pose a risk to native wildlife. [133] However, a German study analysing eggs (n = 289) from Canada geese did not find any Chlamydophila/ Chlamydia bacteria at all. [24] To summarize, geese can harbour the Chlamydia and Chlamydophila bacteria, but there is no evidence that they are a relevant source of infection in poultry, livestock or humans.…”
Section: Respiratorymentioning
confidence: 94%
See 2 more Smart Citations
“…The authors concluded that Canada geese are indeed part of the avian reservoir host system for this bacterium, and that they hence pose a risk to native wildlife. [133] However, a German study analysing eggs (n = 289) from Canada geese did not find any Chlamydophila/ Chlamydia bacteria at all. [24] To summarize, geese can harbour the Chlamydia and Chlamydophila bacteria, but there is no evidence that they are a relevant source of infection in poultry, livestock or humans.…”
Section: Respiratorymentioning
confidence: 94%
“…Zoonotic transfer is linked to inhalation or direct contact. [133] The disease is sometimes referred to as 'psittacosis' or 'ornithosis', depending on the species affected. Birds are the natural reservoir, and transmission of disease between mammals is rare.…”
Section: Respiratorymentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from overt clinical manifestations, latent C. psittaci infection can cause recurrent and chronicity diseases which take an adverse effect on the production performance of animals. Recently, C. psittaci prevalence in birds has been reported around the world [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As in other countries, C. psittaci is highly prevalent in domesticated and wild birds in Belgium (Vanrompay and others 1997, Dickx and others 2010, 2013). Despite its ubiquitous presence in cattle, as is the case in several European countries (Pospischil and others 2002, Borel and others 2006, Kauffold and others 2007, Teankum and others 2007, Kemmerling and others 2009), C. psittaci has not been detected nor looked for previously in Belgian cattle.…”
mentioning
confidence: 63%